PENGARUH BLADDER TRAINING TERHADAP KEMAMPUAN BERKEMIH PASIEN POST OPERASI BENIGN PROSTATIC HYPERPLASIA (BPH) DI RUANG RAWAT INAP DAN POLI UROLOGI RSAL DR. MIDIYATO SURATANI TANJUNGPINANG - Lismawati, Lismawati; Khoriroh, Syamilatul; Ernawati; Sulistia Ayu, Nur Meity (Juru Rawat. Jurnal Update Keperawatan, 2025)
One of the non-pharmacological nursing interventions that can be implemented to prevent urinary incontinence is bladder training. Through bladder training, it is expected to prevent dysfunction and gradually increase bladder capacity as well as extend the interval between urination. This study used a quantitative design with a quasi-experimental approach, employing a pretest and post-test design without a control group. Data were collected from the regular outpatient population at the Urology Clinic of Naval Hospital dr. Midiyato Suratani Tanjungpinang between March 21, 2025, and April 16, 2025, with a total sample of 12 respondents. Sampling was conducted using accidental sampling. The results of the Wilcoxon test showed a p-value of 0.000, indicating that the null hypothesis (H0) was rejected. It can be concluded that bladder training has a significant effect on the urination ability of post-operative benign prostatic hyperplasia (BPH) patients at the Urology Clinic of Naval Hospital dr. Midiyato Suratani Tanjungpinang. Bladder training is effective in helping post-BPH surgery patients manage urination issues. It can improve urinary control by enhancing bladder capacity and strengthening the pelvic floor muscles